1991
DOI: 10.1037/0021-9010.76.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of job characteristics on the acceptability of employee drug testing.

Abstract: Measures of the acceptability of employee drug testing were obtained from a sample of college students (N = 371) and a second sample of nontraditional, older college students (N = 112) and were correlated with job-analysis data from the Position Analysis Questionnaire (PAQ) and Dictionary of Occupational Titles (DOT) databases, and with measures of perceived danger from impaired performance in each job. Both PAQ and DOT data accounted for variance in ratings of acceptability. Perceptions of danger were the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Also, a very specific job description (Management Accountant I) was used in this study; all of the participants were either accounting majors or currently enrolled in an accounting class. Recent research by Murphy, Thornton, and Prue (1991) showed that acceptability of employee drug testing is related to actual job content, with the perception of threats to personal and public safety associated with performance of one's job being the single best-but not the only-predictor of drug-testing program acceptability. The use of a specific job and a sample of participants for whom the job was specifically relevant should have attentuated any contaminating effects of job content on participant responses.…”
Section: Lirnitutionsmentioning
confidence: 99%
“…Also, a very specific job description (Management Accountant I) was used in this study; all of the participants were either accounting majors or currently enrolled in an accounting class. Recent research by Murphy, Thornton, and Prue (1991) showed that acceptability of employee drug testing is related to actual job content, with the perception of threats to personal and public safety associated with performance of one's job being the single best-but not the only-predictor of drug-testing program acceptability. The use of a specific job and a sample of participants for whom the job was specifically relevant should have attentuated any contaminating effects of job content on participant responses.…”
Section: Lirnitutionsmentioning
confidence: 99%
“…Drug screening may have the appearance of a "dragnet" approach, especially the implementation of random drug screening methods (see Hartstein, 1987). It has been suggested that drug testing, in the absence of any compelling reason or explanation, appears to have the potential for creating considerable resentment and other negative feelings among employees (see Murphy, Thornton, and Prue, 1991). In fact, the factors cited above may contribute to the finding that drug screening programs sometimes result in decreased worker productivity (Crouch, Webb, Buller, and Rollins, 1989).…”
Section: Keymentioning
confidence: 99%
“…There are some reports (Maltby, 1990;Murphy et al, 1991) that suggest employees like RTP tests better than biochemical tests. This is probably because of the sense of personal violation related to biochemical testing, as well as its more definitive selfincriminating nature (i.e., positive proof of abused substances).…”
Section: The Impact Of Rtp Testing On the Workermentioning
confidence: 99%
“…23 The extant literature suggests that attitudes towards drug testing are more positive when safety is a major concern. 23,26 In addition, drug testing in safety-sensitive jobs was seen to be less of a violation of privacy than in non-safety-sensitive jobs. In jobs where safety is a major concern, random testing without warning and immediate termination of employment after a positive test may be perceived as fairer than in jobs where safety is not an issue.…”
Section: Attitudesmentioning
confidence: 99%